2008
DOI: 10.1148/rg.286085506
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Clues to Ectopic Pregnancy

Abstract: Ectopic pregnancy accounts for approximately 2% of all pregnancies and is the most common cause of pregnancy-related mortality in the first trimester. Initial evaluation consists of hormonal assays and pelvic ultrasonography (US). A history of pelvic pain along with an abnormal beta human chorionic gonadotropin level should trigger an evaluation for an ectopic pregnancy. The fallopian tube is the most common location for an ectopic pregnancy. An adnexal mass that is separate from the ovary and the tubal ring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
155
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 41 publications
0
155
0
7
Order By: Relevance
“…Ultrasound examination of pelvic organs is widely used to evaluate clinically stable patient suspected of having ectopic pregnancy 22 . In this study 76% patients were diagnosed by ultrasonogram.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound examination of pelvic organs is widely used to evaluate clinically stable patient suspected of having ectopic pregnancy 22 . In this study 76% patients were diagnosed by ultrasonogram.…”
Section: Discussionmentioning
confidence: 99%
“…3 Ultrasonography is remains the principal modality for diagnosis of interstitial pregnancy. 4 Timor-Tritsch et al (1992) for the sonographic diagnosis of interstitial pregnancy suggested to see an "empty uterus with a gestational sac that is seen separately and <1 cm from the most lateral edge of the uterine cavity and a thin myometrial layer surrounding the sac". 5 Tanaka Y et al (2014) emphasized the importance of three-dimensional ultrasonography (3D TVS), 6 with its capacity to reproduce the coronal plane of the uterus and assist the exact localization of the gestational sac relative to the uterine cornu.…”
Section: Discussionmentioning
confidence: 99%
“…Olguların çoğunluğunda yerleşim yeri fallop tüpleridir, tüplerde ise en sık ampuller bölgede meydana gelir. Bunun dışında interstisyel/kornual, ovaryen, servikal, sezaryen skarı ya da abdominal yerleşimli ektopik gebelik de görülebilir [19]. Belirteç olarak serum β-hCG ve progesteron düzeylerinin normal gebeliklere göre daha yavaş artması kullanılır.…”
Section: Ektopik Gebelikunclassified
“…Belirteç olarak serum β-hCG ve progesteron düzeylerinin normal gebeliklere göre daha yavaş artması kullanılır. Görüntüleme öncesi β-hCG düzeyle-rinin bilinmesi önemlidir, çünkü 2000 IU'dan küçük değerlerde normal gebeliklerin US'de görülmesi beklenmez [19,20].…”
Section: Ektopik Gebelikunclassified